Early phase II study of mixed 19‐peptide vaccine monotherapy for refractory triple‐negative breast cancer. Issue 8 (25th June 2020) - Toh, Uhi; Sakurai, Sayaka; Saku, Shuko; Takao, Yuko; Okabe, Mina; Iwakuma, Nobutaka; Shichijo, Shigeki; Yamada, Akira; Itoh, Kyogo; Akagi, Yoshito
Abstract: We undertook an early phase II study of mixed 19‐peptide cancer vaccine monotherapy for 14 advanced metastatic triple‐negative breast cancer (mTNBC) patients refractory to systemic chemotherapy to develop a new type of cancer vaccine. The treatment protocol consisted of a weekly vaccination for 6 weeks, and there were no severe adverse events related to the vaccination throughout the trial. Increase of peptide‐specific IgG against the vaccinated human leukocyte antigen‐matched peptides, but not against the nonmatched peptides, was positively correlated with overall survival (OS) ( P  < .01). The median OS was 11.5 or 24.4 months in all 14 patients or the 10 patients who completed the vaccination. The patients with lower C‐reactive protein levels or 3 or fewer systemic chemotherapies were favorable candidates for this treatment. Advancement of this therapy to the next stage of study could be warranted based on the safety and immune boosting determined herein (clinical trial registration number: UMIN000014616). Abstract : Immune boosting specific to the vaccinated human leukocyte antigen‐matched peptides at the cellular and humoral levels was observed in the vast majority of patients with refractory metastatic triple‐negative breast cancer, who completed all 6 vaccinations.